1999
DOI: 10.1128/aem.65.6.2356-2362.1999
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Immunofluorescence of Regulated eps Gene Expression in Single Cells of Ralstonia solanacearum

Abstract: Ralstonia solanacearum, a phytopathogenic bacterium, uses an environmentally sensitive and complex regulatory network to control expression of multiple virulence genes. Part of this network is an unusual autoregulatory system that produces and senses 3-hydroxypalmitic acid methyl ester. In culture, this autoregulatory system ensures that expression of virulence genes, such as those of the eps operon encoding biosynthesis of the acidic extracellular polysaccharide, occurs only at high cell density (>107 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 56 publications
0
8
0
1
Order By: Relevance
“…Most traits putatively regulated by PhcA have been experimentally verified only in vitro , with the important exception of EPS. Immunofluorescence microscopy of R. solanacearum -infected tomato plants using anti-EPS antibodies demonstrated that EPS production is dependent on cell density in planta ( 23 , 24 ). Accumulating evidence suggests that in vitro studies are not reliable for understanding R. solanacearum regulation during plant pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Most traits putatively regulated by PhcA have been experimentally verified only in vitro , with the important exception of EPS. Immunofluorescence microscopy of R. solanacearum -infected tomato plants using anti-EPS antibodies demonstrated that EPS production is dependent on cell density in planta ( 23 , 24 ). Accumulating evidence suggests that in vitro studies are not reliable for understanding R. solanacearum regulation during plant pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of biofilms is an important factor in the pathogenicity of several organisms [3]. Examples include the biofilm produced by Pseudomonas aeruginosa , an infectious bacterium in humans [4], and those produced by Ralstonia solanacearum , the ESP of which is important for the rapid systemic colonization of tomato plants and the subsequent symptoms caused by bacterial infection [5]. The EPS produced by Xanthomonas campestris may be required for this species’ virulence [6].…”
Section: Introductionmentioning
confidence: 99%
“…On entry, bacterial cells penetrate the xylem vessels and spread throughout the plant establishing foci of infection. The colonizing bacteria cause rot and tissue disintegration through the action of lytic enzymes, extracellular polysaccharides (EPS), endoglucanase (EG) and endopolygalacturonase (PG), which are the major virulence factors (Denny, 1995;Kang et al, 1999). In particular, EPS production contributes to the biomass of colonizing bacteria, resulting in the rapid wilting of infected plants (Saile et al, 1997;Araud-Razou et al, 1998).…”
Section: Introductionmentioning
confidence: 99%